Retrospetiva de um Amor Verdadeiro - Diogo Fernando Pintas Soares (2021)
This report is the culmination of all academic training of teachers. It marks the end and beginning of a long journey. This document narrates the reflective analysis around my pedagogical action in the school world. All my experiences, challenges, frustrations, achievements and knowledge. Here I will show all my performance, as well as my evolution. The professional internship surpassed all my expectations, which were, in itself, quite high. This report is constructed by separate chapters. Initially there will be an introduction, followed by the biographical framework where I show who I am and what my initial expectations are for the EP. Throughout the work comes the framing of professional practice, professional practice and what emerged after the internship experience. In conclusion, I present my final considerations and future perspectives. The construction of this document has a preponderant value in the continuous development of my professional identity.